PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISIONS (STAD) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA KELAS VB SD NEGERI 17 PEKANBARU (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The problem this research is the student achievement of Mathematic studies fifth graderes SDN 17 Pekanbaru still low with an average value of 60,12 and minimum completenness criteria (KKM) mathematic studies is 72. Between students, amounting to 33 people only 18 students who achieve classical KKM with 54,55%. Thir research is Classroom Action Research (CAR), wich aims to improve the learning process in the classroom. Formulation of the problem : is the implementation of Cooperative learning type STAD can improve students achievement of mathematic studies at SDN 17 Pekanbaru. The research was conducted on march 2, 2015 to march 19,2015 by 2 cyclees. Subject were students of SDN 17 Pekanbaru, totalling 33 people who use the data source. The data collection instruments in this research is a teacher and students activities sheets and students achievement. Based on the conduct of research with the implementation of learning models obtained result kooperatif STAD type of activity the teacher in the learning process in cycle I frist meeting was 79,17% and at the second meeting of teacher activity increased by 4,16% to 83,33%. Cycle II frist meeting and the second meeting of activity increased by 4,17% to 87,50% and the second meeting of activity increased by 8,33% to 95,83%. Result of data analysis of students activities in the first meeting cycle with the first meeting of an average of 79,17% and at second meeting of activity increased 4,16% to 83,33%. And a second meeting of activity increased 4,17% improve to 87,50% and the first meeting of the second meeting of activity increased 8,33% to 95,83%. This research presents the results obtained each before the implementation an improve in base score sycle with the average being, 58,79 in the first cycle improve an average of 71,52 with increase as 21,65% and an impove in the second with an average of 80,76 with increase as 37,37%. Result in the research that the implementation of cooperative learning model of STAD can improve students achievement of mathematic studies at fifth graderes SDN 17 Pekanbaru.Key Words : Model Cooperative learning type Student Teams Achievement Divisions (STAD), Hasil Belajar Matematika.